Diversity in Early Childhood Education Through Parents’ Perceptions - Kostas Magos; Konstantina Kalopita (Randwick International of Education and Linguistics Science Journal, 2020)
The management of diversity in preschool framework are today one of the main goals of early childhood education. Ιn addition to the school environment, the family also plays a key role in promoting, or not, the acceptance of diversity. The positions and attitudes of parents employed by their children affect, directly or indirectly, the pedagogical practices that teachers usually develop. The purpose of this research was to investigate the perceptions of parents with preschool children about issues of managing diversity in the context of preschool education. Also, this research aimed to determine whether and to what extent the family environment makes efforts to raise young children’s awareness across cultural diversity. The research emerged that about half of the parents, although they initially invoked a neutral attitude towards the cultural diversity encountered in the kindergarten classes, in their deepest views seem to accept the otherness only if it does not make its appearance clearly visible in the classroom.